Cloning and expression of cystatin, a potent cysteine protease inhibitor from the gut of Haemonchus contortus - NEWLANDS, G.F.J.; SKUCE, P.J.; KNOX, D.P.; SMITH, W.D. (Parasitology, 2001)
A cDNA encoding a cysteine protease inhibitor (cystatin) was identified by immunoscreening a Haemonchus contortus cDNA library with antisera from lambs vaccinated with a protective membrane protein complex (H-gal-GP) derived from the gut of the parasite. The cDNA sequence, designated Cys-1, showed significant levels of similarity with cystatins from several species of nematode as well as with human cystatinNucleotide and amino acid sequence data reported in this paper are available in the GenBankTM database under the accession number AF035945. . Recombinant H. contortus cystatin was expressed in Escherichia coli in a soluble and functionally active form, which proved to be a potent inhibitor of both mammalian cathepsin B and native H. contortus cysteine proteases. Immunolocalization studies using antisera raised against recombinant H. contortus cystatin showed that the inhibitor was predominantly expressed in the cytoplasm of intestinal cells. To determine whether H. contortus had any protective capacity against infection, lambs were vaccinated with the recombinant molecule and subsequently given a single challenge infection. Although vaccination did not confer any protection against infection with H. contortus, as judged by faecal egg output or worm counts, cystatin will be a valuable tool in the analysis of the function of the cysteine proteases which are the subject of on-going study as potential vaccine components.